Whistleblowing System Effectiveness in Fraud Prevention: A Systematic Literature Review Using PRISMA - Santoso, Iwan Fajar; Tanzil, Nanny Dewi (Dinasti Publisher, 2026)
This study systematically reviews the determinants of Whistleblowing System (WBS) effectiveness in fraud prevention using the PRISMA protocol. The study aims to synthesize individual, organizational, and external factors influencing whistleblowing intention and system outcomes, and to identify research gaps in the current literature. A total of 185 peer-reviewed articles published between 2014–2024 were collected through Scopus, Web of Science, ScienceDirect, DOAJ, Google Scholar, and Indonesian national journal databases (Garuda, Neliti, OJS). After applying inclusion and exclusion criteria, 30 studies were retained for qualitative synthesis. Data extraction and coding were conducted by two independent coders using thematic analysis to ensure reliability. The review indicates that retaliation is the strongest negative determinant affecting whistleblowing intention and overall WBS effectiveness. Organizational justice, ethical leadership, management support, and independent reporting channels consistently emerge as positive drivers. External legal protection and digital anonymity features significantly improve reporting behavior. The review also identifies four major research gaps: conceptual integration, contextual applicability, methodological diversity, and regulatory inconsistencies. This study proposes an integrative theoretical model combining the Theory of Planned Behavior (TPB), Organizational Justice Theory, and Institutional Theory to explain WBS effectiveness. Practical recommendations are provided for strengthening WBS implementation in public and private organizations.